IMPLIKASI UNDANG-UNDANG SISTEM PENDIDIKAN NASIONAL DALAM PENYELENGGARAAN LEMBAGA PAUD - Sri Mulyani; Umi Faizah (STPI Bina Insan Mulia Yogyakarta, 2022)
The Indonesian government's attention to the world of education is increasing from time to time. Through the establishment of the Law on the National Education System, the government carried out the mandate of the opening of the 1945 Constitution in the context of the intellectual life of the nation. Early Childhood Education (PAUD) in Indonesia has finally got its own part in the National Education System Law which shows the commitment of the Indonesian people to organize early childhood education for children from birth to the age of 6 years. In Law no. 20 of 2003, namely in Chapter IV, the seventh part on Early Childhood Education, it is explained that early childhood education is held before basic education, either through formal channels (TK, RA, etc.), non-formal (KB, TPA, etc.), informal (family education or education organized by the environment). In addition, the implementation of early childhood education must also be adjusted to Chapter III concerning the principles of implementing education, article 4 paragraph 1-6 of Law no. 20 of 2003. This regulation is implicated in 4 principles of implementing PAUD, namely holistic and integrated, scientifically based, oriented to child development, and community oriented; without abandoning the principles of early childhood learning including playing while learning, oriented to children's needs, integrated stimulation, oriented to child development, conducive environment, using a thematic approach, PAKEM principles (Active, Creative, Effective, and Fun Learning), and using various media and learning resources.